2003
DOI: 10.1007/bf03179918
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and impaired glucose tolerance in obese children and adolescents

Abstract: In developed countries, obesity prevalence has strongly increased in the last decades. This has also been observed in children and adolescents. Until recently, type 2 diabetes mellitus was considered very rare among children and adolescents; however, in the last decades, some cases have been observed mainly in obese adolescents of some minority populations. The aim of our study was to assess the prevalence of type 2 diabetes, impaired glucose tolerance (IGT) and insulin resistance, and the metabolic features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 30 publications
2
29
0
10
Order By: Relevance
“…The prevention and treatment of obesity among children and adolescents are important to reduce the risk of health complications in both childhood and adulthood. 3,4 Selection of risk groups would also be suitable for optimisation of economic resources.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention and treatment of obesity among children and adolescents are important to reduce the risk of health complications in both childhood and adulthood. 3,4 Selection of risk groups would also be suitable for optimisation of economic resources.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In Taiwan, the rate of diagnosis of T2DM in the screening program was 0.9 percent and 1.53 percent in boys and girls, respectively in community level. 19 Prevalence of prediabetes was 19.2 percent in 280 overweight Japanese children.…”
Section: Impaired Glucose Tolerance (Igt) and Type 2 Diabetes Mellitumentioning
confidence: 99%
“…[15][16][17][18]22 Study conducted in New Delhi has found the prevalence of IGT to be 18.2 percent amongst obese children.8 Increasing prevalence of type 2 diabetes among children in India and other counties has been attributed to epidemic of obesity and overweight among children. Sinha and colleagues have reported the prevalence of impaired glucose tolerance to be 21 percent amongst obese adolescents in the U.S.22 Similarly, study done in Germany has reported a prevalence of IGT as 36.3 percent and T2DM as 5.9 percent amongst obese adolescent.…”
Section: Bmimentioning
confidence: 99%
“…Bu çalışmada, insülin direncinde gruplar arasında anlamlı fark görülürken BAG ve BGT arasında fark gösterilmemiştir. Literatürde çocuklarda obezite ile ilişkili insülin direnci ve glukoz metabolizması bozukluklarının sıklığı ile ilgili çok farklı sonuçlar yayınlanmıştır (25)(26)(27)(28)(29)(30)(31)(32). Çalışmalar arasındaki farklar, çalışma için seçilen populasyon, yaş dağılımı, coğrafi şartlar ve beslenme alışkanlıkları ile direkt olarak ilişkili görünmektedir.…”
Section: Klinik Bulguunclassified